Restorative Rehabilitation of a Patient with Dental Erosion - Mohammed Thamer AlShahrani; Satheesh B. Haralur; Mohammed Alqarni (Case Reports in Dentistry)
Dental erosion is the chemical dissolution of the tooth structure. Factors like eating disorders and gastrointestinal diseases are recognized as intrinsic factors for dental erosion. Advanced stages of dental erosion extensively damage the tooth morphology, consequently affecting both esthetics and functions. Reports indicate the growing prevalence of erosion, and hence knowledge of restorative rehabilitation of tooth erosion is an integral part of the contemporary dental practice. This clinical report describes an adult patient with gastroesophageal reflux induced dental erosion involving the palatal surface of the maxillary anterior teeth. The extensive involvement of the palatal surfaces compromised the esthetics, incisal guidance, and functional occlusal efficiency. Indirect all-ceramic restorations were utilized to restore the esthetics and occlusal reconstruction. In conclusion, patients affected by severe dental erosion require prosthetic rehabilitation besides the management of the associated medical condition.